Gut microbiome and fecal metabolic alteration in systemic lupus erythematosus patients with depression - Yao, Han; Yang, Hao; Wang, Yueying; Xing, Qian; Yan, Lin; Chai, Yaru (Frontiers in Cellular and Infection Microbiology, 2022)
Background: Mental health disorders in systemic lupus erythematosus (SLE) are gradually getting recognized; however, less is known regarding the actual structure and compositional alterations in gut microbiome and metabolism and the mechanisms of how they affect depression development in SLE patients. Methods: Twenty-one SLE patients with depression (SLE-d), 17 SLE patients without depression (SLE-nd), and 32 healthy controls (HC) were included in this study. Fecal samples were collected for 16S rRNA gene sequencing and ultra-high-performance liquid chromatography-quadrupole time-of-flight mass spectrometry (UHPLC-QTOF-MS) based metabolomics. Results: The structure of gut microbiome in the SLE-d group changed compared with that in the other two groups. The microbiome composition of SLE-d group showed decreased species richness indices, characterized by low ACE and Chao1 indices, a decrease in the ratio of phylum Firmicutes to Bacteroidetes, genus Faecalibacterium and Roseburia. A downregulation of the metabolite fexofenadine involved in bile secretion was positively correlated with the genus Faecalibacterium, Subdoligranulum and Agathobacter. Compared with the SLE-nd group, the SLE-d group had elevated serum levels of IL-2 and IL-6 and decreased BDNF. Interestingly, abundance of the genus Faecalibacterium and Roseburia was negatively correlated with IL-6, abundance of the genus Roseburia was negatively correlated with IL-2, and abundance of the genus Bacteroides was positively correlated with IL-2. Conclusion: This study identified specific fecal microbes and their metabolites that may participate in the development of SLE-d. Our findings provide a new perspective for improving depression in SLE patients by regulating the gut–brain axis.